Muscari zagricum (Asparagaceae, Scilloideae), a unique new species from Iran - Ali̇pour, Sajad; Maji̇di̇, Rami̇ar; Eker, İsmai̇l (Phytotaxa, 2024)
A new species, Muscari zagricum Eker, Alipour & Majidi (Asparagaceae) from Iran, is described and illustrated. It has no closely related species, and is partly similar to M. pseudopallens and M. pallens, but differs from them mainly in morphological characters such as outer tunic color, raceme shape and density, pedicels no extending when in fruit, shape of fertile flowers with shouldered and grooved, color when dry, color of lobes, strongly compressed capsule valves, as well as flowering time and habitat characteristics. In this study, a comprehensive description, diagnostic characters, original photographs, geographical distribution, conservation assessment, and taxonomic comments on the new species are presented.